O jogo de intermediações enunciativas no romance de Alan Pauls - Baldan, Maria de Lourdes Ortiz Gandini [UNESP] (My University, 2012)
The novel O passado (2003) by Alan Pauls presents many isotopies which would deserve to be investigated: there is a varied construction of loving relationships among the characters, who reveal different feelings, that would allow a mapping of passions to be studied; there is an activity of translation (role performed by Rimini and Carmen) that engenders a very rich reflection on the literary activity which is taking place. There is also the presence of a visual artist, Jeremy Riltse, revealing a poetic work which was created by this discourse. Due to the dimension that a research of this kind would require, it is not possible to deal with all the isotopies. Thus, the last one was chosen to be investigated, that is, to verify how the fictional visual artist and his singular work operate in the novel.

O romance O passado (2003) de Alan Pauls apresenta muitas isotopias que mereceriam ser investigadas: há uma construção variada de relacionamentos amorosos entre os personagens com sentimentos diferentes, que permitiriam um mapeamento de paixões a serem estudadas; há uma atividade de tradução (ofício desempenhado por Rimini e Carmen) que engendra contornos muito ricos na reflexão sobre a atividade literária que está se realizando. E há a presença de Jeremy Riltse, artista plástico criado por esse discurso, com uma poética completa. Um trabalho com a dimensão que este pretende ter, não conseguiria tratar de todas elas. Ficamos apenas com a última, ou seja, verificar como o artista plástico ficcional e sua obra singular funcionam no romance.
The play on enunciative intermediations in Alan Pauls’ novel
Keywords: Enunciation; Contemporary Narrative; Literature and other Arts; Enunciação; Narrativa Contemporânea; Literatura e outras Artes